Utility of bioelectrical phase angle for cardiovascular risk assessment among individuals with and without diabetes mellitus - Tsilingiris, Dimitrios; Schimpfle, Lukas; Kender, Zoltán; Sulaj, Alba; Rauchhaupt, Ekaterina von; Herzig, Stephan; Szendrödi, Julia; Kopf, Stefan (Diabetes & vascular disease research, 2024)
Purpose - Low values of bioimpedance-derived phase angle (PA) have been associated with various adverse outcomes. We investigated the association of PA with cardiovascular markers in individuals with and without diabetes mellitus (DM). - Methods - PA was measured in 452 adults (without DM n = 153, T1DM n = 67, T2DM n = 232). Carotid intima-media thickness (IMT), renal resistive index (RRI), ankle-brachial index (ABI) and carotid-femoral Pulse Wave Velocity (cfPWV) were estimated. Furthermore, the levels of high-sensitive Troponin-T [hsTnT], N-terminal brain natriuretic peptide [NT-pro-BNP]) were measured. - Results - PA values were lower in DM independently of age, gender, and BMI (estimated marginal means 6.21, 5.83, 5.95 for controls, T1DM, T2DM p < .05), a finding which persisted after propensity score matching. PA correlated negatively with IMT (r = −0.181), RRI (r = −0.374), cfPWV (r = −0.358), hsTnT (r = −0.238) and NT-pro-BNP (r = −0.318) (all p < .001). In multivariable analysis, the associations with RRI, cfPWV, hsTnT and NT-pro-BNP remained unchanged. PA values 6.0-6.5° for males and 5.2-5.8° for females were predictive of commonly used cutoffs. The combination of ΑCC/AHA ASCVD Score with PA outperformed either factor in predicting cfPWV, RRI for males and hsTnT, BNP for both genders. - Conclusions - PA exhibits independent correlations with various parameters pertinent to cardiovascular risk and may be useful for cardiovascular assessment.
Vorab online veröffentlicht: 2. Februar 2024
Gesehen am 10.06.2024